Peran Kompetensi Instruktur dalam Menyampaikan Materi Pelatihan kepada siswa di Perguruan ANNIDA Al Islamy : Kajian Profesional, Kepribadian, dan Sosial - Herman Bedi Agtriadi; Dewi Arianti Wulandari; Indrianto; Meilia Nur Indah Susanti; Abdurrasyid; Rahmad Evan (Politeknik Piksi Ganesha Indonesia, 2025)
This community service aimed to improve training quality for senior high school students by enhancing instructors’ professional, personal, and social competencies. Activities included training, observation, and evaluation using a Likert-scale questionnaire distributed to 24 participants. Results showed that 50% of respondents rated instructors’ readiness and organization as Very Good, and 37.5% as Good. Professional competence, such as topic explanation, received Very Good ratings from 45.8%, while social competencies like communication and tolerance were rated Very Good by 37.5% and Good by 50%. The average score across all indicators was above 4.25 (on a scale of 1–5). These findings indicate a positive impact on training effectiveness and student engagement. This program contributes to creating more interactive and meaningful training sessions, aligning with the learning needs of today’s students.